Sharia Board of Islamic Banks and the Attitude of Fatwa Shopping - Salisu, Auwal; Saniff, Shereeza Mohamad; Hassan, Shahir Akram (Universitas Islam Negeri Raden Intan Lampung, 2020)
Fatwa shopping attitude is a process of searching Sharia opinions from different Sharia scholars for suitable and convenient Fatwa to suit the need of bank managers (BMs) even at the minimum level of Sharia compliance. This research was conducted to identify the Sharia Board Members (SBMs) and the new attitude of Fatwa shopping within the supervisory and advisory mandate. The objectives of this study are to identify the mandate of SBMs of IBs and to review the attitude of Fatwa shopping within the advisory and supervisory mandate. Data was collected by way of documentary review method of existing literatures, narrative analysis as well as conceptual approach of analysis. The study gathered that both SBMs and BMs have different objectives when assessing new products which create disagreement of objectives at the strategic level. The study concluded that the leniency in issuing Fatwa ruling might lead SBMs to exercise the attitude of Fatwa shopping or easily compromise toward BMs objectives. A situation of this kind has resulted many challenges toward Sharia complaint, then the products approved by SBMs which have been alleged as non-compliant to Sharia. The findings of this paper can be recommended for regulators, policy makers of Islamic banks and the body of knowledge of researchers for positive use of conceptualizing the current system to suit core component of Islamic Fatwa framework (IFF) in which the attitude of Fatwa shopping would be matter of history in near future.